Kelapa Sebagai Sarana Ungkitan Ekonomi Keluarga - Neni Meidawati (Rahmatan Lil 'Alamin Journal of Community Services, 2023)
The aim of Community Service is to provide education for housewives to make soap with Natural and Organic Soap Brands. Empowering housewives in supporting the fulfillment of the household economy is very important to create prosperity and peace in the household. The method is by conducting training and inviting competent people in the field of making organic soap. The introduction of products produced from home industries to housewives is expected to be a family economic leverage, by utilizing materials in the family environment that are easily available and affordable. Coconut is a plant that is easy to obtain and can grow easily everywhere. Hopefully with the soap-making training, the home industry products can grow and develop from the smallest scale, namely the household, to create a strong economy because it starts from the smallest group, namely the family.